2008
DOI: 10.1517/14712598.8.7.885
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal cells for skeletal tissue engineering

Abstract: Background : Skeletal defects represent a significant socioeconomic burden to the US healthcare system. Current options for reconstructing osseous deficits have shortcomings. Objective : To review the use of mesenchymal stem cells for skeletal tissue engineering. Methods : We focused on the application of mesenchymal cells in skeletal regeneration, optimization of this technique, tropic effects of multipotent mesenchymal cells, and future directions. Results/conclusion : A number of cell-based modalities have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 68 publications
(44 reference statements)
0
14
0
1
Order By: Relevance
“…Based on the principle of bone tissue engineering, seeding cells, scaffolds, and signaling molecules are administered, individually or in combination, to regenerate new bone. Mesenchymal stem cells (MSCs), for both self renewal and being multipotent, have been regarded as the most hopeful cell sources for bone tissue engineering and regenerative medicine (Abreu et al, 2002;Howard et al, 2008;Slater et al, 2008;Xiang et al, 2007). To enhance the proliferation and orientational differentiation ability of stem cells by gene modification is hot in bone tissue engineering (Mauney et al, 2005;Goessler et al, 2006;Meijer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the principle of bone tissue engineering, seeding cells, scaffolds, and signaling molecules are administered, individually or in combination, to regenerate new bone. Mesenchymal stem cells (MSCs), for both self renewal and being multipotent, have been regarded as the most hopeful cell sources for bone tissue engineering and regenerative medicine (Abreu et al, 2002;Howard et al, 2008;Slater et al, 2008;Xiang et al, 2007). To enhance the proliferation and orientational differentiation ability of stem cells by gene modification is hot in bone tissue engineering (Mauney et al, 2005;Goessler et al, 2006;Meijer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow MSCs are attractive in bone tissue engineering, for it can be easily isolated and further modified by gene modification (Pelled et al, 2002;Pountos et al, 2007;Slater et al, 2008). Many genes had been regulated or overexpressed in MSCs to improve their ability of differentiation into osteoblastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs, for its ability to differentiate to multiple lineages, specifically, their osteogenic potential and their immunomodulatory, anti-inflammatory and anti-apoptotic properties, have become a major tool in cell therapy for the regenerative treatment of pathologies affecting functionally bone tissue [76][77][78][79]. In vitro analyzes show that MSCs induced by osteogenic differentiation medium increase the expression of osteogenic differentiation markers such as alkaline phosphatase, osteocalcin, osteopontin, bone sialoprotein and calcium deposits in the extracellular matrix.…”
Section: Mesenchymal Stem Cells-based Therapymentioning
confidence: 99%
“…However, the political and ethical issues associated with hESCs have cast a shadow of doubt over their realistic potential for implementation in tissue engineering strategies (3). Thus, mesenchymal stem cells/multipotent stromal cells (MSCs) have emerged as a promising cell source in the ongoing research of bone tissue engineering (4). Numerous studies have demonstrated that MSCs derived from various origins, including skin, hair follicle, periosteum, bone marrow, adipose tissue, umbilical cord blood, and so on, are able to differentiate into various phenotypic lineages, such as cartilage, bone, fat, and nerve in vitro and in vivo (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%